Implementation of Smart Agrologistics in Fish Wrapped in a Banana Leaf Business to Increase the Income of Freshwater Fishermen Post-Covid19 - Rindra Yusianto; Iswoyo; Amalia; Herwin Suprijono (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Fish wrapped in a banana leaf is one of the processed fish commodities caught by superior fishermen from Wadaslintang, Central Java. After COVID-19, several obstacles emerged at the Wadaslintang Fish Craftsmen, namely the procurement of raw materials for red tilapia (Oreochromis niloticus) and the marketing of the products. Its activity aims to apply innovative agrologistic technology with a spatial database. Activities were carried out for eight months for 15 KUB members. The method of implementing the activity is interviews and implementation of segregation and georeferencing digitization of the distribution of quality raw material providers, potential market segments, and optimization of marketing area coverage. The results of the implementation of activities show that this technology can be applied well to build a productive fishing community civilization. The number of new business ventures increased from 15 to 20 members, marketing reach expanded to Semarang, and production increased from 60kg/day to 150kg/day.